2020
DOI: 10.1037/apl0000831
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and well-being during COVID-19: A resource-based examination.

Abstract: M. (2016). The effect of job insecurity on employee health complaints: A within-person analysis of the explanatory role of threats to the manifest and latent benefits of work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
183
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(235 citation statements)
references
References 73 publications
19
183
2
3
Order By: Relevance
“…Regarding the socioeconomic level, group comparisons showed that the high impact cluster had a worse socioeconomic level than medium and low impact ones. While lower socioeconomic level has been identified as a risk factor associated with mental health issues (e.g., Jones et al, 2016), recent research specifically addressing the impact of the pandemic suggests that people with higher incomes experienced a greater relative decrease in well-being during lockdown (Wanberg et al, 2020). In line with this relative perception of loss, our results also showed group differences regarding training conditions during confinement, with the high impact cluster showing worse training conditions than the low impact cluster.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Regarding the socioeconomic level, group comparisons showed that the high impact cluster had a worse socioeconomic level than medium and low impact ones. While lower socioeconomic level has been identified as a risk factor associated with mental health issues (e.g., Jones et al, 2016), recent research specifically addressing the impact of the pandemic suggests that people with higher incomes experienced a greater relative decrease in well-being during lockdown (Wanberg et al, 2020). In line with this relative perception of loss, our results also showed group differences regarding training conditions during confinement, with the high impact cluster showing worse training conditions than the low impact cluster.…”
Section: Discussionsupporting
confidence: 79%
“…Group differences regarding academic course showed that participants in the high impact cluster were pursuing higher academic courses than the low impact one. Research in this line suggested that individuals with higher academic level usually report lower levels of well-being (Wanberg et al, 2020). Within the sports field, previous evidence relates mental health issues with higher difficulties to undertake a dual career pathway (Sallen et al, 2018;Sorkkila et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These findings notably complement but also problematize some prior studies that signal contrasting well-being impacts of the Covid-19 pandemic based on socioeconomic factors such as income and education (Wanberg et al, 2020), or occupation (Recchi et al, 2020), or even precarious/vulnerable positions (Apouey et al, 2020;Enriquez and Goldstein, 2020;Jaspal and Breakwell, 2020;Wang et al, 2020). The fact that we did not find any one socioeconomic or occupational factor to predict profile membership implies that, at least in this type of crisis, employee well-being is likely to differ also within and not just across socioeconomic groups.…”
Section: Discussionsupporting
confidence: 71%
“…While these studies imply that less affluent workers are more at risk for poor health and well-being due to the pandemic, others indicate that higher socioeconomic status does not necessarily protect subjective well-being during lockdown. For example, a study conducted in the United States found that higher education was related to a greater increase in depressive symptoms and a decrease in life satisfaction during the pandemic (Wanberg et al, 2020 ). Studies also show that some precarious workers did not experience increased stress or anxiety during the first wave of the pandemic (Apouey et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This positive correlation can be explained by the enormous uncertainty caused by the COVID-19 pandemic. Prior literature established that anxiety is a future-oriented mood state, in which individuals anticipate a highly likely unpleasant crisis (Eysenck et al 2006 ; Finlay-Jones and Brown 1981 ) and high-income individuals have a stronger expectation for a constant availability of resources (Wanberg et al 2020 ). During the pandemic, the expectation of constantly available resources is seriously challenged.…”
Section: Resultsmentioning
confidence: 99%